Математическое моделирование перорального теста толерантности к глюкозе с двойной нагрузкой по Штаубу – Трауготту - Лапта, Станислав Сергеевич (Друкарня Мадрид, 2018)
This paper presents the first mathematical modeling of an oral glucose tolerance test with a double load, used for qualitative diagnosis of latent Diabetes mellitus type 2. Based on the clinical and physiological data of the carbohydrate exchange regulation system, its structural-functional minimal model in the form of the first- order differential equation with delayed argument relative to the glycemic level, that adequately reproduces the data of this test, is constructed.
Keywords: диагностика заболеваний; медицинская диагностика; углеводный обмен; математическая модель